W/AlSiTiNx/SiAlTiOyNx/SiAlOx multilayered solar thermal selective absorber coating - AL-Rjoub, A. (2020)
Solar thermal energy has often been used as a renewable green energy source. Here we present a design composed of a highly selective solar thermal absorber coating that has been deposited by DC magnetron sputtering. This will consist of four layers: W/AlSiTiNx/SiAlTiOyNx/SiAlOx. The coating that was utilised revealed an excellent average solar thermal absorbance, (alpha = 95.5%) with very low emittance, (epsilon = 9.6% calculated for 500 degrees C) together with an excellent thermal stability after annealed at 500 degrees C, in air for 350 h, and at 630 degrees C in vacuum for 220 h.